PERBUATAN PENCEMARAN NAMA BAIK MELALUI MEDIA/SARANA ELEKTRONIK (PUTUSAN NOMOR 104/PID/2020/PT BNA) - Jeremy Pradana Marpaung; Dian Adriawan Tawang (Faculty of Law, Universitas Trisakti, 2023)
Defamation is an act of tarnishing one's reputation through spoken or written statements. The problem addressed is how the defendant's act of defamation through electronic media/means is dealt with in the decision number 104/PID/2020/PT BNA, and whether the verdict in decision number 104/PID/2020/PT BNA aligns with the elements of Article 27, paragraph (3) of the ITE Law (Information and Electronic Transactions Law). In providing answers to the problem, a normative juridical research method is employed using secondary data. The research findings are analyzed qualitatively. The results of the research and discussion indicate that Saiful Mahdi's act of defamation does not conform to Article 27, paragraph (3) of Law No. 11 of 2008 concerning Information and Electronic Transactions. Based on the analysis of the core issue, the judge should have applied Article 310, paragraph (2) of the Indonesian Criminal Code (KUHP), which deals with attacking someone's honor or reputation in writing. The conclusion drawn from this research is that Saiful Mahdi's act of defamation should have been judged under Article 310, paragraph (3) of the KUHP, as he wrote the statement in question with the aim of defending the public interest to prevent misunderstandings at the Faculty of Engineering, Unsyiah